Resource-based theories of competitive advantage: A ten-year retrospective on the resource-based view - Barney, Jay B. (Journal of Management, 2001)
The resource-based view can be positioned relative to at least three theoretical traditions: SCP-based theories of industry determinants of firm performance, neo-classical microeconomics, and evolutionary economics. In the 1991 article, only the first of these ways of positioning the resourcebased view is explored. This article briefly discusses some of the implications of positioning the resource-based view relative to these other two literatures; it also discusses some of the empirical implications of each of these different resource-based theories.